Evaluating ethane and methane emissions associated with the development of oil and natural gas extraction in North America. (7th April 2016) - Franco, B; Mahieu, E; Emmons, L K; Tzompa-Sosa, Z A; Fischer, E V; Sudo, K; Bovy, B; Conway, S; Griffin, D; Hannigan, J W; Strong, K; Walker, K A
Abstract: Sharp rises in the atmospheric abundance of ethane (C2 H6 ) have been detected from 2009 onwards in the Northern Hemisphere as a result of the unprecedented growth in the exploitation of shale gas and tight oil reservoirs in North America. Using time series of C2 H6 total columns derived from ground-based Fourier transform infrared (FTIR) observations made at five selected Network for the Detection of Atmospheric Composition Change sites, we characterize the recent C2 H6 evolution and determine growth rates of ∼5% yr −1 at mid-latitudes and of ∼3% yr −1 at remote sites. Results from CAM-chem simulations with the Hemispheric Transport of Air Pollutants, Phase II bottom-up inventory for anthropogenic emissions are found to greatly underestimate the current C2 H6 abundances. Doubling global emissions is required to reconcile the simulations and the observations prior to 2009. We further estimate that North American anthropogenic C2 H6 emissions have increased from 1.6 Tg yr −1 in 2008 to 2.8 Tg yr −1 in 2014, i.e. by 75% over these six years. We also completed a second simulation with new top-down emissions of C2 H6 from North American oil and gas activities, biofuel consumption and biomass burning, inferred from space-borne observations of methane (CH4 ) from Greenhouse Gases Observing SATellite. In this simulation, GEOS-Chem is able to reproduce FTIR measurements at the mid-latitudinal sites, underscoring the impact of the North American oil and gas development on the current C2 H6 abundance. Finally we estimate that the North American oil and gas emissions of CH4, a major greenhouse gas, grew from 20 to 35 Tg yr −1 over the period 2008–2014, in association with the recent C2 H6 rise.